Three Classes of Antioxidant Defense Systems and the Development of Postmenopausal Osteoporosis - Yang, Keda; Cao, Fangming; Xue, Yuchuan; Tao, Lin; Zhu, Yue (Frontiers in Physiology, 2022)
Osteoporosis is a common bone imbalance disease that threatens the health of postmenopausal women. Estrogen deficiency accelerates the ageing of women. Oxidative stress damage is regarded as the main pathogenesis of postmenopausal osteoporosis. The accumulation of reactive oxygen species in the bone microenvironment plays a role in osteoblast and osteoclast apoptosis. Improving the oxidative state is essential for the prevention and treatment of postmenopausal osteoporosis. There are three classes of antioxidant defense systems in the body to eliminate free radicals and peroxides including antioxidant substances, antioxidant enzymes and repair enzymes. In our review, we demonstrated the mechanism of antioxidants and their effect on bone metabolism in detail. We concluded that GSH/GSSG conversion involved the PI3K/Akt-Nrf2/HO-1 signaling pathway and that the antioxidant enzyme mediated mitochondrial apoptosis pathway of osteoblasts was necessary for the development of postmenopausal osteoporosis. Since the current therapeutic effects of targeting bone cells are not significant, improving the systemic peroxidation state and then regulating bone homeostasis will be a new method for the treatment of postmenopausal osteoporosis.